Disaster education - Shaw, Rajib; Shiwaku, Koichi; Takeuchi, Yukiko (Community, environment and disaster risk management ;, 2011)
Education is the key to risk reduction, be it environmental management or disaster risk reduction, and is a process which needs to be embedded at different levels of management and practices to collectively reduce the risk. While school education forms the foundations of the knowledge cycle, for effective knowledge use, it is necessary to link school and community education. Education is linked to enhanced awareness and a key reflection of education is seen in terms of actions. Divided into four sections this book begins with an informative introduction to the subject of disaster risk reduction education and proceeds to highlight key places of education such as family, community, school, and higher education. It then examines approaches, methods and tools before providing a future perspective and pointing to the way ahead. This is the first book of its kind on disaster risk reduction education. A ready reference for practitioners in the field this book describes and demonstrates different aspects of education in an easy-to-understand form with current academic research and practical field experiences included throughout.